战争历史与建构 ：中美韩战历史记忆的比较 = War, memory and history : the Korean war in China and America - 许樱娴 Hui, Yeng Hung (2015)
战争的历史记忆在国家里扮演着很重要的角色，而很多时候这些战争历史记忆都是由国家所掌控的。本文通过对官方文章、媒体报章、纪念空间等媒介里的韩战历史叙事的分析，去探讨中国和美国个别如何去建构一个符合自己国家需要的韩战历史记忆和叙事。另外，本文也进一步比较中国和美国的韩战历史记忆，从而呈示中美之间韩战历史记忆的异同之处，以及它们与国家、历史、记忆与建构的关系。 War and its memories has always been shaped and controlled by the nation state. Through analyzing the Korean War memories in official narratives, media, memorials and other agencies, this paper discusses the role of the nation states, China and America, in shaping and making the history and memories of the Korean War in their countries. By comparing the Korean War memories and narratives in both China and America, this paper further discusses their similarities and differences, and thus their relations with the politics of war memory and commemoration.